Determination of Sectoral Economic Growth on Educated Unemployment in All Provinces of Indonesia (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2022)
One of the characteristics of unemployment in Indonesia is the high number of educated unemployed but economic growth is increasing every year. This is certainly caused by concern because ideally when the economy is growing unemployment should decline but the reality is not. This study aims to analyze: 1) The effect of economic growth on educated unemployment, 2) What industries can reduce educated unemployment. This type of research is ex post facto. The object of research is 34 provinces in Indonesia using panel data. Hypothesis testing uses panel data regression. The research findings prove that: 1) Economic growth has a significant negative effect on educated unemployed graduates of high school and academy and economic growth has a significant positive effect on vocational high school and university graduates. That is, when economic growth increases, educated unemployed graduates from high school and academy will decrease but increase for graduates of vocational high schools and universities. 2) Industries that can reduce educated unemployment are the electricity and gas procurement industry and the financial and insurance services industryDetermination of Sectoral Economic Growth on Educated Unemployment in All Provinces of Indonesia